Trust Effects on E-commerce: Cross-cultural Comparison of Business-to-Consumer Environment Between UK and China - Xu, Tiantian (2016)
The advent of the internet has changed the way of conducting business due to the unique nature of the web and internet such as ubiquity, global reach, interactivity, personalization and so on (Laudon and Laudon, 2009). As a result, E-commerce has been becoming a more attractive avenue to conduct business. At the same time, the trust is also becoming increasingly important element in the success of transaction in virtual environment. While many scholars have made many study contributing in this field, but they do not conduct in the way of qualitative one. Most them just find the generalization of the samples. In addition, some international trust also be discussed. In this study, B2C e-Commerce was used to understand the effect of trust in the online shopping in China and UK. The results of the existing research may not have a direct application to China and UK. Semi-structured interview was used to collect data in this research. The Chinese or British consumers who have online shopping experience were chosen to do the interview. According to findings, internet merchant should have trustworthiness features including benevolence, integrity, and ability, which are the important factors in the formation of trust for both Chinese and British online customers. For customers themselves, their individual propensity to trust, culture and perceived usefulness and perceived ease of use are associated with their trust and purchasing intention. Furthermore, some external environment such as guarantees from the third parties and legal environment the still has influence on customer trust and shopping behavior. In addition, different trust factors also have different influencing degree on consumers’ purchasing behavior.